Instances of Islamophobia : demonizing the Muslim "other" - Mirhosseini, Seyyed-Abdolhamid; Rouzbeh, Hossein (Lexington Books, 2015)
"Chapters of this volume, written by authorities on Islamophobia from around the world, examine various instances of the topic and explore different discursive contexts such as media coverage and manipulation; political debates and discourses; and general attitudes and attitude-building in the public sphere. The book aims to further extend and expand discussions on the issue and to highlight some hitherto less discussed concerns"--Provided by publisher